A Novel L-ascorbate Peroxidase 6 Gene, ScAPX6, Plays an Important Role in the Regulation of Response to Biotic and Abiotic Stresses in Sugarcane - Liu, Feng; Huang, Ning; Wang, Ling; Ling, Hui; Sun, Tingting; Ahmad, Waqar; Muhammad, Khushi; Guo, Jinxin; Xu, Liping; Gao, Shiwu; Que, Youxiong; Su, Yachun (Frontiers in Plant Science, 2018)
The L-ascorbate peroxidase 6 gene (APX6) is one of the most important genes for scavenging H2O2 and plays a vital role in plant resistance to environmental stresses. In this study, a novel ScAPX6 gene (GenBank Accession No. KT907352) was obtained from a sugarcane variety (ROC22). Bioinformatics analysis showed that ScAPX6 has a cDNA length of 1,086 bp and encoded 333 amino acid residues. Subcellular localization confirmed that ScAPX6 was located in the chloroplast. Enhanced growth of Escherichia coli BL21 cells that expressed ScAPX6 showed high tolerance under copper (Cu) stress. Real-time quantitative PCR analysis revealed that ScAPX6 was constitutively expressed wherein with the highest expression levels in sugarcane pith and leaf and the lowest in the root. ScAPX6 was down-regulated by salicylic acid (SA), hydrogen peroxide (H2O2), polyethylene glycol (PEG) and sodium chloride (NaCl) stimuli. Interestingly, it was significantly up-regulated under the stresses of abscisic acid (ABA) and methyl jasmonate (MeJA) wherein with the highest inducible expression levels at 6 h at 6.0– and 70.0–times higher respectively than that of control. Overexpression of ScAPX6 in Nicotiana benthamiana leaves enhanced the resistance to the infection of tobacco pathogens Pseudomonas solanacearum and Fusarium solani var. coeruleum. These results implied that ScAPX6 might positively respond to ABA, MeJA and Cu, but might negatively respond to the stresses of SA, H2O2, PEG, and NaCl. Keeping in view the current investigation, ScAPX6 could be associated with the hypersensitive response (HR) or immunity of sugarcane, which will provide a baseline for the function identification of sugarcane ScAPX6.